Paradeterminants and partition polynomials - Zators’kyi, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study Bell polynomials by using functions of triangular matrices (parapermanents and paradeterminants). Some combinatorial identities and relationships between these functions and the Stirling numbers of the first and second kinds are established.